Increased Contributions of Microbial Extracellular Polymeric Substance to Soil Organic Carbon During Grassland Degradation - Haolin Zhang; Ji Chen; Yang Hu; Xiaoxiang Sun; Jiacong Zhou; Yubin Wang; Bicheng Zhang; Kyungjin Min; Sergey Blagodatsky; Shaoshan An; Zhaolong Zhu (Global Change Biology, 2026)
Microbial residues are fundamental to the long‐term stabilization of soil organic carbon (SOC). Intensively used alpine grasslands are subject to degradation under climate change, which may profoundly reshape microbial life‐history strategies and SOC accumulation. However, the mechanisms by which grassland degradation influences the accumulation of different microbial residues and by which microbial life‐history strategies regulate these processes remain unclear. Addressing this research gap, we quantified microbial necromass carbon (MNC) and extracellular polymeric substance carbon (EPSC) and assessed their contributions to SOC in grasslands under different stages of degradation. We also investigated the impact of microbial growth and resource acquisition strategies on the accumulation of MNC and EPSC. We found that microbial residues were differentially influenced by grassland degradation. On average across the lightly, moderately, and heavily degraded grasslands, MNC declined by 69% relative to the non‐degraded grassland, whereas EPSC declined by only 15%. Interestingly, grassland degradation increased the ratio of EPSC to microbial biomass carbon by 1.4‐fold and its contribution to SOC by 1.2‐fold. The higher ratio of EPSC to microbial biomass carbon is indicative of rapid microbial biomass turnover, which in turn promotes EPSC's contribution to SOC. Enhanced EPSC accumulation under degradation was associated with shifts in microbial life‐history strategies, such as reduced carbon use efficiency, elevated metabolic quotient, and increased production of carbon‐acquisition enzymes. In contrast, there were no significant differences in the ratio of MNC to microbial biomass carbon or its contribution to SOC under the varying degradation intensity. In conclusion, this study provides novel and direct empirical evidence that EPSC plays an important role in SOC accumulation in degraded grasslands.